A Study of Various Aspects of Internet Financial Reporting: A Case of Malaysian Auditors - Azli, Mohd Noor (Information Management and Business Review, 2013)
The objective of this research is to analyse the important items in the disclosure of benefit IFR to company and users, factors companies to engage or not engage IFR and some audit issues that can be used to describe the level of IFR from auditor’s perception. Questionnaires were distributed to 100 auditors. A total of 40 questionnaires were completed and returned, giving a response rate of 40 percent. Based on the literature review of the IFR from the survey towards auditors indicate three items of benefit IFR to user are helps users in the decision-making process, provides accessibility to the users, increase timeliness and efficiency in obtaining financial information. Meanwhile, three items on benefit IFR towards company are attract foreign investors, attract local investors, and promote company wider to the public. On the other hand, three factor influence companies to engage IFR because enhancement of corporate image, stability and improvement in share prices and competitors in the industry. Whilst, three-factor Company not to engage IFR because requires expertise from the company, concerned over disclosure of propriety information and concerned over security information. Finally, the findings of this study also cover audit issues, for example the conversion or transposition processes involved in publishing information on the internet is susceptible to error, information on the internet is exposed to access and modification by unauthorised users both external and internal to the reporting entity and that information on the internet has the potential to be very fluid. Lastly, the limitation of this study was also highlighted and there are suggestions for future research.